MICAL2 Promotes Proliferation and Migration of Glioblastoma Cells Through TGF-β/p-Smad2/EMT-Like Signaling Pathway - Pu, Bei; Zhang, Xu; Yan, Tengfeng; Li, Yuntao; Liu, Baohui; Jian, Zhihong; Mahgoub, Omer Kamal; Gu, Lijuan; Xiong, Xiaoxing; Zou, Ning (Frontiers in Oncology, 2021)
Recent studies showed that Molecule interacting with CasL2 (MICAL2) could be a novel tumor growth factor and it is closely associated with tumor growth and invasion. However, the role it plays in glioblastoma (GBM) and its potential mechanisms are currently unknown. Our study is designed to identify the effect of MICAL2 on GBM cells and the potential mechanisms behind it. Here we found that MICAL2 interacts with TGF receptor-type I (TGFRI) and promotes the proliferation and migration of glioblastoma through the TGF-β/p-Smad2/EMT-like signaling pathway. MICAL2-knockdown inhibited the proliferation of glioblastoma cells, which was related to cell cycle arrest and downregulation of DNA replication. The invasion abilities of U87 and U251 cells were reduced after the knockdown of MICAL2. MICAL2 promoted the growth of GBM in nude mice. High MICAL2 predicts poor outcome of GBM patients. MICAL2 could be identified as a novel promising therapeutic target for human GBM.